(untitled) (Tanzania Medical Journal, 2010)
Background: Cross infection can be defined as the transmission of infectious agents by inhalation or inoculation between patients and staff within a clinical environment. Aim: The study determined patients’ knowledge and attitude towards cross infection in dental practice. Materials and Methods: The convenient cross-sectional study included 200 patients aged 15 years and above attending a missionary dispensary at Mbagala, Dar es Salaam. Following consent, a structured questionnaire explored patient’s knowledge and attitude towards cross infection in dental practice. Epi Info 2002 was used for analysis and a p-value less than 0.05 was used to determine level of significance. Results: Of the 200 respondents, majority (n=154;77%) had knowledge on cross infection during dental treatment, especially in regard to HIV/AIDS (n=126,63%) followed by fungal infections (n=85;42.5%) and syphilis (n=34;17%). The patients also knew that transmission of disease could occur through air droplets (n=163;81.5%) or blood and body fluids (n=191;95.5%). They also knew that gloves (n=178;89%), face masks (n=166;83%) and sterilization (n=190;95%) could prevent transmission of disease. Respondents were of the attitude that regardless of the practitioners’ health status protective gears should be worn (n=167;83.5%) and sterilization of the environment done (n=183;92.5%) so as to prevent cross infection. Also one should have the right to refuse treatment if at risk of being infected (n=119;59.5%). Conclusion: Majority of patients have knowledge that cross infection can occur during dental treatment and knowledge on HIV/AIDS is more in comparison to other diseases like syphilis and fungal infections. Generally most respondents had a positive attitude, however, many were of the opinion that they would agree to be treated by a known infected doctor regardless of not using protective gear. This portrays a need to educate patients on cross infection in dental clinics.Key Words: Knowledge, attitude, cross infection, dental practice, Tanzania.